1981
DOI: 10.1007/bf02679324
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid‐ phospholipid interaction in soybean oil

Abstract: Phospholipid‐phospholipid interaction in soybean oil is described. Phosphatidylcholine was effectively removed from soybean oil by degumming (water hydration), whereas phosphatidylethanolamine and phosphatidic acid were hardly hydratable. However, the degree of their hydration increased in the presence of phosphatidylcholine. The spectrophotometric assay based on charge transfer interaction between 7,7,8,8‐tetracyanoquinodimethane and phospholipids at 480 nm was used to determine the formation of phospholipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…It was observed that there was a significant reduction in the phospholipid content to 261.5 ppm from 612.66 ppm with 5 w/w OPA p 0.05 . However, higher strength of acid beyond 5 OPA, did not show a significant reduction in the phospholipid content p 0.05 and tends to make the oil darker in colour by decomposing non-hydratable phospholipids to form brown sludge 28 . Hence, 5 OPA was chosen for degumming of crude sardine oil.…”
Section: Degummingmentioning
confidence: 83%
“…It was observed that there was a significant reduction in the phospholipid content to 261.5 ppm from 612.66 ppm with 5 w/w OPA p 0.05 . However, higher strength of acid beyond 5 OPA, did not show a significant reduction in the phospholipid content p 0.05 and tends to make the oil darker in colour by decomposing non-hydratable phospholipids to form brown sludge 28 . Hence, 5 OPA was chosen for degumming of crude sardine oil.…”
Section: Degummingmentioning
confidence: 83%
“…The quality and quantity of PC in the lecithin primarily decide its applications. Among the various phospholipids present in the vegetable oils, PC has the lowest critical micelle concentration (CMC) (14) and hence exhibits the highest surfactant activity. Therefore, the HOSF oil model solution containing the principal phospholipid (PC) could be considered close to the real system.…”
Section: Resultsmentioning
confidence: 99%
“…In that instance, the Zwitterion would be removed on water degumming leaving the molecule without charges in the oil. Further Zwitterions would then be formed so that on subsequent water degumming, further PE would be removed (Kanamoto et al, 1981). However, this is just speculation on my part.…”
Section: Phosphatide Behaviour During Oil Milling Degumming and Neutmentioning
confidence: 97%